Morphological, biochemical and transcriptomic characterisation of Chlorella sorokiniana and Chlorella zofingiensis during normal and stress conditions - Azaman, Siti Nor Ani (2017)
Chlorella has been identified as one of the most interesting microalgae species, which has high nutritional values, high growth rate, and is able to produce a wide range of metabolites in response to environmental changes. The objectives of this study are to characterise the morphology and biochemical contents and to identify the genes and miRNAs involved in regulating the production of carotenoids and lipids in Chlorella sorokiniana and Chlorella zofingiensis when cultured under high light intensity combined with glucose supplementation. In this study, stress was introduced to the Chlorella cultures by adding 2% glucose and increasing the light intensity from 10 to 100 μmol photons m-1 s-1. Then, the pigments, total phenolic contents, and antioxidant activities of both Chlorella species were evaluated. The results showed that both strains grew larger when cultured under stress condition. Although the total carotenoid content was increased under stress condition, reduction of the pigment and total phenolic contents associated with lower antioxidant activity were also recorded. Subsequently, the transcriptome of C. sorokiniana was sequenced using Illumina paired-end sequencing, and 198,844,110 raw reads with the length of 100 bp were produced. After pre-processing, ~95% of high quality reads were de novo assembled using Trinity software into 18,310 contigs. Analysis of differential gene expression by DESeq2 package showed that a total of 767 genes were upregulated and 948 genes were downregulated in stress conditions. Then, miRNAs that regulate the genes during normal and stress conditions of both C. sorokiniana and C. zofingiensis were profiled and analysed using CLC Genomic Workbench and OmiRas. From both analysis pipelines, the known and predicted novel miRNAs were identified. Although most of the identified miRNAs were not functionally determined, this study suggests that they were species-specific, which may have roles in regulating genes during stress condition. In conclusion, identifying the genes and the regulation of various metabolite productions under different growth conditions are useful for further strain enhancement of the microalgae.